New material of Dicynodon angielczyki (Synapsida: Anomodontia) from Mozambique and Zambia with biostratigraphic implications for African Permo-Triassic basins. Issue 6 (2nd November 2021) - Kammerer, Christian F.; Araújo, Ricardo; Cumbane, Keila; Macungo, Zanildo; Smith, Roger M. H.; Angielczyk, Kenneth D.
ABSTRACT: Dicynodont therapsids are widely used in Permo-Triassic vertebrate biostratigraphy. However, recent taxonomic revisions have left few valid species with broad enough geographic distributions to use in establishing interbasinal correlations; instead, most currently recognized dicynodont species are basinal endemics. This is particularly true of the array of Permian dicynodontoids held in the formerly cosmopolitan wastebasket genus Dicynodon, now considered to mostly represent distinct (and in many cases distantly related) local taxa. As an example, Dicynodon fossils from the Ruhuhu Basin of Tanzania, formerly referred to " Dicynodon huenei, " have recently been separated out as a distinct species, Dicynodon angielczyki . Dicynodon angielczyki has been considered a Ruhuhu Basin endemic, as no records of this taxon are known in the extensive dicynodont sample from the Karoo Basin of South Africa. However, there has been little research on dicynodontoids from other upper Permian basins in eastern Africa, and their taxonomic composition is uncertain. Here, we describe the first specimens referable to D . angielczyki from other African sedimentary basins, demonstrating that this species is also present in the Metangula Graben of Mozambique and Luangwa Basin of Zambia. The new specimens permit improved correlations between the rock units of these basins as well as providing new information on the anatomy and possibly ontogeny of D . angielczyki .